KAJIAN YURIDIS UPAYA HUKUM PERSAINGAN USAHA DALAM MENCIPTAKAN KESEIMBANGAN ANTARA KEPENTINGAN PELAKU USAHA DAN PERLINDUNGAN KONSUMEN - Yuniarti, Rahmi; Berlian, Cheny (UIR Law Review, 2024)
Business competition law and consumer protection law have relevance in that the positive impact that occurs from healthy competition impacts business actors and consumers, as well as the negative impact that occurs if there are monopolistic practices and unfair business competition. Apart from business actors, consumers will also experience loss. The problem studied in this article is a Juridical Study of Legal Efforts for Business Competition in Creating a Balance Between the Interests of Business Actors and Consumer Protection. The approach method that will be used is normative juridical. This research is descriptive analytical in nature and the results of data processing are then analyzed using qualitative descriptive methods. Consumer rights are closely related to business competition. If unfair competition occurs and consumers become victims, consumers have the right to receive compensation. Consumers also have the right to receive appropriate advocacy, protection and efforts to resolve consumer protection disputes. It would be better if monopolistic practices and unfair business competition occur, consumers can immediately claim their rights in this case without needing to file a lawsuit for compensation again. Keywords : Business Competition Law, Business Actors, Consumers